The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1007/bf02731735
|View full text |Cite
|
Sign up to set email alerts
|

Benign acute childhood myositis

Abstract: Benign acute myositis occurs often in association with viral infection. In the present study, Dengue virus was positive in 20 (50%) children. Benign acute myositis can be differentiated from more serious causes of walking difficulty by presence of calf and thigh muscle tenderness on stretching, normal power and deep tendon reflex and elevated CPK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
50
1
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 7 publications
2
50
1
6
Order By: Relevance
“…The pain is particularly pronounced when the patient first gets up in the morning. In the etiology, there are often Influenza type A and B viruses, RSV, adenoviruses, HSV, EBV, or CMV [4,5]. In our case, we did not test these when forming the differential diagnosis because there were no symptoms suggestive of viral upper respiratory tract infection.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…The pain is particularly pronounced when the patient first gets up in the morning. In the etiology, there are often Influenza type A and B viruses, RSV, adenoviruses, HSV, EBV, or CMV [4,5]. In our case, we did not test these when forming the differential diagnosis because there were no symptoms suggestive of viral upper respiratory tract infection.…”
Section: Introductionmentioning
confidence: 88%
“…Since patients complain about an inability to walk, stand up, and step onto their feet, all families become extremely worried about their children and refer to the emergency departments of hospitals. Rajajee et al reported that cases of BACM are most frequently directed to the clinic with a preliminary diagnosis of GBS [5]. However, in GBS, a two-sided muscle weakness and pain moving upward is observed, decreased deep tendon reflexes are detected in physical examination, and serum CPK level is within normal limits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In addition, trauma, severe exercise, drug reactions, metabolic disorders and status epilepticus cause rhabdomyolysis. Rhabdomyolysis is characterized with sudden muscle pain, inability to walk or difficulty in walking and elevated serum creatine phosphokinase (CPK).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and laboratory finding rare resolved spontaneously within one week. [1][2][3] Due to the clinical findings of rhabdomyolysis, differential diagnosis should be made with pyomyositis, muscular dystrophy, Guillain-Barre syndrome, transverse myelitis, meningitis and other diseases Recurrent rhabdomyolysis in a child. Case presentation such as postinfectious cerebellitis.…”
Section: Introductionmentioning
confidence: 99%